Nadużycie praw procesowych w postępowaniu cywilnym – zagadnienia ogólne: [Abuse of procedural rights in civil proceeding – general issues] (Studia Prawnicze / The Legal Studies, 2012)
Nadużycie prawa jest zagadnieniem towarzyszącym ludzkim społecznościom od chwili, gdy zaczęto posługiwać się prawem. Oznacza zastosowanie, użycie danego narzędzia prawnego sprzecznie z celem, dla którego zostało ono utworzone, niezgodnie z jego przeznaczeniem. Od najdawniejszych czasów próbowano stosować różne środki zaradcze, mające zapobiegać nadużyciu prawa, długo jednak nie zdawano sobie sprawy z możliwości skonstruowania dla zjawiska nadużycia prawa odrębnej kategorii prawnej. Najwcześniej doszło do tego w odniesieniu do prywatnego prawa podmiotowego, wkrótce jednak, wraz z odkrywaniem i wyodrębnianiem kolejnych dziedzin prawa, rodziła się potrzeba posługiwania się pojęciem nadużycia prawa na nowych obszarach. Dlatego też wraz z rozwojem prawa, jego urządzeń i instytucji, coraz bardziej skomplikowane stało się również i staje się w dalszym ciągu, zagadnienie nadużycia prawa.Doniosłość zagadnień związanych z nadużyciem prawa w sposób szczególny uwidacznia się w dziedzinie prawa postępowania cywilnego, a zwłaszcza procesu cywilnego. Prawo procesowe cywilne, choć cechuje się odrębnością i autonomią, to jednak ma za zadanie zapewnić urzeczywistnienie norm prawa materialnego w praktyce, a więc ogólnie mówiąc, zapewnić stosowanie prawa w państwie i społeczeństwie. Wszędzie zaś tam, gdzie wchodzi w grę realne stosowanie prawa, w sposób szczególny uwidaczniają się problemy związane z jego nadużyciem. W procesie cywilnym może więc dojść do nadużycia prawa podmiotowego, co będzie miało miejsce, gdy jedna ze stron będzie korzystać z tego prawa w sposób wykraczający poza określone czynniki, wyznaczające w istocie jego granice. Niezależnie od tego sama konstrukcja i urządzenie procesu cywilnego sprawiają, że on sam jako taki i funkcjonujące w jego ramach instytucje prawa procesowego i uprawnienia procesowe mogą zostać wykorzystane przez uczestników postępowania cywilnego niezgodnie z celami, dla których zostały przewidziane przez ustawodawcę. Dlatego należy uznać, że rozważania dotyczące nadużycia praw procesowych są tak samo istotne dla nauki i praktyki prawa, jak zagadnienia związane z nadużyciem praw podmiotowych. Civil proceeding is a field in which the problem of abuse of rights is an issue of significant importance because it concerns many legal aspects and institutions i.e. the right to court access (the right to action and the right to defence), abuse of substantive rights, fictitious trial (disputes), procedural acts, other procedural conducts, the role of court, relations between the party and its litigation lawyer, etc. The main and general observations and conclusions drawn from analyses of all these aspects as well as many others are as follows: 1. APR intrinsically constructs a ban, under which any abusive conducts are forbidden. APR also provides an obligation under which every participant of civil proceeding is bound to act and behave properly, honestly and in accordance with good faith and principles of social coexistence. APR as a ban preventing any kind of abuse should be regarded as a binding civil procedure principle. Its existence is justified by: – the general provisions: art. 3 of the Polish civil procedure code – “pcpc” (which obliges participants of a proceeding to submit true facts without hiding anything and to conduct procedural acts in accordance with good customs), art. 45 para. 1 of the Polish Constitution and ratified international treaties (the European Convention on Human Rights and the International Covenant on Civil and Political Rights); – the specific provisions of pcpc which analytically deal with conducts that are directly forbidden or sanctioned; – the concept of procedural relationship – and more precisely by, derived from this concept, the duty of procedural fairness; – the aim and essence of civil procedure, the purpose of which is to provide the protection and enforcement of justified claims (in the private and public interest). This principle can also be derived from many other principles of law, e.g. principles of social coexistence, fairness, due process of law, justice, democratic legal state, good faith, cooperation, equality, safety of legal transactions, effectiveness of proceeding. Having existed in the spheres of these principles it binds them axiologically and praxeologically. The distinction of the principle banning any abuses in civil proceeding is an important factor in theory and practice of law. It helps to perform the proper interpretation and application of the specific pcpc provisions. Thanks to this principle it becomes obvious that legal institutions cannot be used in contradiction to aims for which they were constructed. 2. The discussed principle shall not be confused with the clause which bans the abuse of substantive rights (art. 5 Polish civil code – “pcc”), because the latter is a substantive law norm and cannot be applied to purely procedural situations. These two legal constructs should be clearly distinguished, as they are often confused, especially in practice of law. However, the substantive law clause of art. 5 pcc can also be applied to procedural acts but only to these of them which simultaneously constitute acts of material law (e.g. in case of judicial settlement) and only through specific procedural provisions (e.g. art. 203 of pcpc). 3. The principle itself, as every principle of law, does not provide any specific sanctions. Sanctions may be applied only if they are stipulated by the specific regulations (rules), which indicate given instances of abuse and their possible legal consequences. Therefore these rules exemplify the existence of the principle. Only the responsibility for the cost of proceeding can be regarded as a sanction of general nature, especially for the willful cost, because under art. 103 par. 1 and 2 of pcpc one who intentionally causes the costs should be held responsible regardless of the outcome of the trial. It must be pointed out that the best sanctions for procedural abuses are repressive measures, especially monetary fines, because their imposition well proportionate to the importance of the abuse is an effective means for the prevention of APR. Sanctions such as ineff ectiveness, nullity, voidness, etc., shall not be considered due to two reasons. Firstly, because they are useless in case of abuses which do not constitute procedural acts. Secondly, they would cause the state of constant uncertainty on the validity and effectiveness of the parties’ procedural acts. 4. It must be observed that de lege lata no kind of legal consequences can be applied with regard to abuse of right to access to court. In Polish legal system the right to court is a constitutionally guaranteed fundamental, public substantive right of every human being. Therefore, it cannot be limited. Every claim or defence must be essentially, not only formally, tried, even if it is manifestly illfounded and absurd. This state is not satisfactory. Thus, the implementation of some foreign solutions into Polish law is worth of consideration. One of them is the institution of vexatious litigant known in common law systems. Thanks to it, the persons who constantly and recklessly use their right to court can be officially declared as vexatious litigants and depicted in the special public register. That means that they cannot initiate or join any judicial proceeding without court’s consent. Also the scope of civil liability could be widened under Polish law. This kind of amendment would unable courts to find a party who litigates unfairly responsible for compensation of any damage sustained by her opponent. 5. APR concerns different kinds of acts and conducts which can be classified into three groups. The first includes punishable abuses of procedural entitlements performed with formally legitimate procedural acts. The second contains unfair conducts (acts and omissions carried on before or inside the proceedings) which affect the proper course or outcome of the trial and against which the specific consequences can be applied by the court. The third concerns unpunishable abuses which cannot cause any sanctions, however, they violate the general principle of APR. 6. The clause of APR cannot be referred to the activity of the court itself because abuse concerns only the use of right. The court does not exercise any rights but only fulfils public law obligations. Therefore, if the court makes mistakes, applies the substantive or procedural law incorrectly and uses its authority improperly, it means only that the obligations were not fulfilled but not that rights were abused. These mistakes may only constitute the grounds for appeals. 7. As far as the relationship between a party and its representative (mainly a professional litigation lawyer) is concerned, it must be underlined that generally it is the party who is responsible and charged with consequences of her lawyer’s improper conduct. However, notwithstanding the fact that in some cases he also can be the subject of punishment (art. 110 and art. 214 par 3 pcpc), under Polish law the range of sanctions should be widened. 8. Another important aspect of APR concerns so-called “fictitious trial”. In Polish doctrine of law this term is widely used for a proceeding in which parties are in conspiracy (collusion) in order to deceive the court and get its awarding adjudication. Because the plaintiff ’s claim is imaginary, so in fact does not exist and the conspiring parties cooperate instead of litigate. Therefore the defendant does not arrange defense or simply confesses that the claim is true, and the court awards the plaintiff with the final decision. The real aim of this conspiracy is mostly to harm the real creditor of the defendant. The plaintiff in fact is a friend and a trustee of the defendant whose aim is to keep and safe assets with the use of the court’s decision issued in that trial. This kind of conduct is in contradiction to justice and a glaring example of abuse of litigation. The term “fictitious trial” is not proper although it has been commonly used for a long time. Whereas a claim and a dispute declared within the proceeding can in fact be fictitious, a judicial trial itself cannot be regarded as such. The court as the State authority is real, the parties are real, the proceeding is real. If we describe a trial as fictitious, we actually question the role and esteem of the court as an organ of State. Therefore, the new term should be suggested for this kind of abuse i.e. “fixed trial”. However, the old name can remain in use because of its long presence in legal literature but only with the awareness of its imperfection. Under pcpc there are some instruments which could prevent the conspiring parties from reaching their aim but they are insufficient. However, what is more important, there is no instrument which allow to challenge the essential decision issued in a fixed trial. When a decision is final even extraordinary procedural remedies like cassation or petition for resumption of proceeding cannot be used. Therefore, the provisions concerning the latter institution should be amended. Under this proposal the public prosecutor or the Human Rights Defender will be authorised to submit a petition with the justification that the final decision was issued in a fixed trial.